Canine H3N8 influenza vaccines partially protect mice against the canine H3N2 strain currently circulating in the United States - Willis, Elinor; Parkhouse, Kaela; Krammer, Florian; Hensley, Scott E. (Vaccine, 2016)
•Canine H3N8 vaccines elicit antibodies that react strongly to canine H3N2 viruses.•Abs elicited by canine H3N8 vaccines bind to the HA stalk region of canine H3N2.•Canine H3N8 vaccines partially protect mice against canine H3N2 infection. Influenza A viruses infect many species and cross-species transmission occurs occasionally. An equine H3N8 influenza virus began circulating in dogs in 1999 and an avian H3N2 influenza virus began circulating in dogs in 2006. The canine H3N8 (cH3N8) viral strain has become endemic in parts of the United States and there is a commercially available vaccine against this strain. The canine H3N2 (cH3N2) strain did not circulate widely in the United States until 2015. Here, we used a mouse model to determine if the cH3N8 and cH3N2 strains are antigenically related and if a commercially available cH3N8 vaccine protects animals against the cH3N2 outbreak strain. We find that the cH3N8 vaccine elicits antibodies that react to internal viral proteins and the hemagglutinin stalk region of cH3N2 viruses. These antibodies do not provide sterilizing immunity against cH3N2 infection, but these antibodies limit cH3N2 replication in the lung.